2019
DOI: 10.1111/ajag.12608
|View full text |Cite
|
Sign up to set email alerts
|

Use of medicines that may precipitate delirium prior to hospitalisation in older Australians with delirium: An observational study

Abstract: Objective To assess the use of medicines associated with delirium prior to hospital admission in older Australian patients with a recorded diagnosis of delirium. Methods A retrospective observational study was conducted using de‐identified data from the Australian Government Department of Veterans’ Affairs Health Care Claims Database. The prevalence of use of medicines associated with delirium was determined in people 65 years or older with a delirium diagnosis. Results Three‐quarters of the total 22 923 older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…4,7,11 This pooled result also demonstrated that older patients had an increased risk of developing POD, which may be due to poor physical condition, more comorbidities, and complex medication use in senile patients. [32][33][34] Unfortunately, our results indicated high heterogeneity in age. After subgroup analysis, heterogeneity decreased by 80%, but the significance did not change, which can be explained by the small sample size.…”
Section: Demographic Predictorscontrasting
confidence: 69%
See 1 more Smart Citation
“…4,7,11 This pooled result also demonstrated that older patients had an increased risk of developing POD, which may be due to poor physical condition, more comorbidities, and complex medication use in senile patients. [32][33][34] Unfortunately, our results indicated high heterogeneity in age. After subgroup analysis, heterogeneity decreased by 80%, but the significance did not change, which can be explained by the small sample size.…”
Section: Demographic Predictorscontrasting
confidence: 69%
“…Age has been well‐established as an independent predisposing factor for POD 4,7,11 . This pooled result also demonstrated that older patients had an increased risk of developing POD, which may be due to poor physical condition, more comorbidities, and complex medication use in senile patients 32–34 . Unfortunately, our results indicated high heterogeneity in age.…”
Section: Discussionmentioning
confidence: 52%
“…Among the most investigated mechanisms is cholinergic dysfunction, which may contribute to some of the manifestations known to be present in delirium, such as cognitive deficits associated with memory loss [7,8]. Identification and reversal of clinical conditions associated with delirium are the first step to treat the disturbance, as well as mitigation of environmental factors and the exposure to deliriogenic drugs [9]. Non-pharmacological approaches should be provided in order to prevent and manage the neuropsychiatric symptoms related to delirium, such as: avoid the use of physical restraints, catheters, and bed alarms, ambulate patient, address sensory impairment, encourage exposure to bright light during the day, among others [8].…”
Section: Definition Diagnosis and Treatmentmentioning
confidence: 99%
“…Thus, in order to prevent the development of delirium resulting from the use of drugs, it became necessary to develop risk management plans, which is currently a prerequisite for a good pharmacovigilance service [9].…”
Section: Delirium In Older Peoplementioning
confidence: 99%
“…Older adults are at an increased risk of delirium because of ageing, multiple comorbidities, frailty, and polypharmacy 11,16–18 . Medication‐induced delirium is a modifiable risk factor, and studies have shown several individual medications can contribute to delirium in older adults 19–22 . Some of the most common medications classes associated with delirium include antimicrobials, antihistamines, antihypertensives, anticholinergics, antidepressants, antipsychotics benzodiazepines, diuretics, opioids, and nonsteroidal anti‐inflammatory medications 23–27 .…”
Section: Introductionmentioning
confidence: 99%